Artificial Intelligence, Marketing, and the History of Technology: Kranzberg's Laws as a Conceptual Lens. Issue 1 (February 2023) - Pitt, Christine; Paschen, Jeannette; Kietzmann, Jan; Pitt, Leyland F.; Pala, Erol
Killer applications, or killer apps, are technology applications that profoundly change the way any society thinks, works, and functions. This paper explores Artificial Intelligence (AI) as a killer app, with specific application to marketing. Specifically, this paper employs the lens of technology history to explore the relationship between marketing and AI. Using Kranzberg's six laws of technology, this paper sheds light on all manner of innovations, how technologies have shaped and impacted society, and how marketers can respond to this. This inquiry offers two main contributions: First, it suggests a number of implications for marketing practice and scholars, derived from each of Kranzberg's laws. These suggestions are intended to guide marketing practice when implementing or using AI. In addition, this article offers a number of research directions that might be fruitful and important areas for investigation in future scholarly work regarding technology's impact among marketing scholars.